Validation of a CD30 Enzyme-Linked Immunosorbant Assay for the Rapid Detection of Breast Implant-Associated Anaplastic Large Cell Lymphoma. (21st February 2019) - Hanson, Summer E; Hassid, Victor J; Branch-Brooks, Cynthia; Liu, Jun; Kadin, Marshall E; Miranda, Roberto; Butler, Charles E; Clemens, Mark W
Abstract: Background: Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is an uncommon type of non-Hodgkin lymphoma occurring in the fluid or capsule adjacent to textured breast implants. Diagnosis of BIA-ALCL of symptomatic patients requires demonstration of large anaplastic cells with uniform expression of CD30 protein on immunohistochemistry. Objectives: The authors investigated a novel, rapid, office-based, and economic in-situ enzyme-linked immunosorbent assay (ELISA) for screening BIA-ALCL patients. Methods: A commercially available in-situ ELISA was standardized and validated for patients with confirmed BIA-ALCL diagnosis with clinical isolates. A panel of 9 pathologically confirmed BIA-ALCL patients was screened by serum, plasma, and periprosthetic effusion specimens and compared against serum, plasma, and nonneoplastic delayed seromas in 7 control patients. Statistical analysis demonstrated assay consistency and reliability. Results: All BIA-ALCL effusions demonstrated CD30 ELISA detection at full and all serial concentrations. BIA-ALCL serum specimens and all control specimens were negative at full concentration and serial dilutions (1:100, 1:250, 1:500, and 1:1000). BIA-ALCL plasma specimens were weakly positive at full concentration and revealed no activity with serial dilution. Conclusions: This is the first study to demonstrate a viable alternative to CD30 immunohistochemistry for the screening of BIA-ALCL. Our study demonstrates 100% sensitivity in seroma fluid with no detectable CD30 in benign seroma samples. A CD30 ELISA represents a novel, low-cost screening test, which may be used to screen suspicious aspirations of delayed periprosthetic fluid collections in an office-based setting. Level of Evidence: 3: